Equity research - bayer ag: the post-merger era - Moreira, José Miguel Fernandes (2022)
Following the acquisition of Monsanto, Bayer’s market capitalization suffered a huge hit, as it dropped to values lower then the all-cash acquisition price. By acquiring the business, Bayer also acquired the risks and faced several lawsuits that implied settlements of over €13 bn in the last years. Despite this, the prospects for Bayer’s Crop Science are positive, with mega trends driving the potential growth in revenues. There are threats from competitors, such as Corteva in the soybean seeds market, but also promising new products, such as the revolutionary short stature corn that can solidify the position of Bayer as market leaders in the Agricultural Inputs market. The Consumer Health business unit has its roots imprinted in the launch of Aspirin TM in the 19thcentury, a product that is still sold nowadays and even though the competition is high, with several substitutes, its still a relevant product in Bayer’s portfolio. Favorable growth in the Nutritionals segments and increasing e-commerce constitute the key trends that Bayer will be focused on. The recent dark times for Bayer may conceal a bright future in the post-merger era.